Environmental Ecology of the Palembayan Watershed – Agam Regency - Petrizal Petrizal; Eni Kamal; Isril Berd; Abdul Razak (Science and Environmental Journal for Postgraduate, 2022)
The Palembayan Watershed as an object of study, in the 2011 RTRW of the Agam Regency, is one of the watersheds in the Agam Regency, an area that must maintain the authenticity of its environmental ecology, from studies and research the raw water quantity can be calculated and potential, very high quality raw water needs to be maintained , starting from upstream to downstream in the Landian watershed, it is necessary to carry out guidance, integrated conservation of all sectors so that it is maintained according to its function.